Deskrypcja długości pięciu łuków podłużnych stóp kobiet w wieku od 4 do 18 lat w świetle mory projekcyjnej - Mirosław Mrozkowiak (Kazimierz Wielki University, 2015)
Mrozkowiak Mirosław. Deskrypcja długości pięciu łuków podłużnych stóp kobiet w wieku od 4 do 18 lat w świetle mory projekcyjnej = Length description of five longitudinal arches of foot burdened with its weight on the basis of female population at the age between 4 and 18 in the light of projection moire. Journal of Education, Health and Sport. 2015;5(9):283-292. ISSN 2391-8306. DOI10.5281/zenodo.30629 http://dx.doi.org/10.5281/zenodo.30629 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A283-292 https://pbn.nauka.gov.pl/works/621602 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.08.2015. Revised 05.09.2015. Accepted: 08.09.2015.   Deskrypcja długości pięciu łuków podłużnych stóp kobiet w wieku od 4 do 18 lat w świetle mory projekcyjnej   Length description of five longitudinal arches of foot burdened with its weight on the basis of female population at the age between 4 and 18 in the light of projection moire   Mirosław Mrozkowiak   Uniwersytet Kazimierza Wielkiego, Instytut Kultury Fizycznej Bydgoszcz e-mail: magmar54@interia.pl strona: http://wadypostawy.republika.pl   Słowa kluczowe: długość, łuk podłużny, wysklepienie stopy.   Streszczenie Wstęp. Wszystkie łuki dynamiczne składające się na sklepienie podłużne w rozwoju osobniczym wykazują podobną tendencję, dużą indywidualizację i zróżnicowanie wysokości. Wskazuje na to wysoka wartość współczynników zmienności wysokości łuków, ich analiza pozwala zaobserwować pewną prawidłowość. Największe wartości występują u dzieci młodszych i dotyczą głównie wysklepienia łuków V i IV. Cel pracy. Określenie przebiegu zmian długości pięciu łuków wysklepienia podłużnego stóp populacji żeńskiej w wieku od 4 do 18 lat regionu Warmińsko - Mazurskiego. Materiał i metody. Badaniami objęto populację dziewcząt 9804 w wieku od 4 do 18 lat, z wybranych losowo przedszkoli i szkół regionu Warmińsko - Mazurskiego. Metodyka badań obejmowała pomiar długości pięciu łuków dynamicznych wysklepienia podłużnego stopy lewej i prawej. Do oceny wykorzystano stanowisko do komputerowej oceny postawy ciała, techniką mory projekcyjnej  - Posturometr M. Wyniki. Rezultaty badań przedstawiono na ryc. 1 - przebieg zmian średnich wartości długości 5 łuków stóp populacji żeńskiej. Dla porównania przedstawiono na ryc. 2 - przebieg zmian średnich wartości długości 5 łuków stóp populacji obojga płci. Stwierdzenia      1. Okres pierwszy to intensywny rozwój długości I, II, III, IV i V łuku podłużnego stopy          prawej i lewej występuje od 5 do 12 r. ż. Drugi okres od 12 do 16 r.ż. to czas względnej          stabilizacji. Trzeci od 16 do 18 r.ż. długości zmniejszają się      2. I, II i V podłużny łuk stopy prawej od 4 do 6 r.ż. jest dłuższy niż w stopy lewej. W          okresie od 6 do 8 r.ż długość łuków I, III i IV stopy lewej jest większa, w okresie od 8          do 17 r.ż. długość łuku I, II i V jest większa w stopie prawej, III do 16 r.ż., dalej          wszystkie zmniejszają swoją długość      3. Łuki I, II, III, IV i V obu stóp mają podobny przebieg rozwoju. Łuk I jest najdłuższy,          dalej odpowiednio II i III, łuk IV i V są zdecydowanie krótsze.   Keywords: length, longitudinal arch, foot arch.   Summary Introduction. All dynamic arches comprising the longitudinal foot arch in the individual development show a similar tendency, considerable individualization and diversification of height. This is shown by a high value of arch height coefficients of variation, their analysis allows observing a certain regularity. The highest values are found in the case of younger children and mainly refer to foot arches V and IV. Aim. Specifying the course of changes in the lenght of five longitudinal arches of foot on the basis of female population at the age between 4 to18 in the Warmińsko-Mazurski region. Subjects and methodology. The research covers the population of 9804 women at the age between 4 and 18 from nursery and other schools selected randomly and located in the Warmińsko-Mazurski region. The research methodology covered the length measurement of five dynamic longitudinal arches of the right and left foot. For the purpose of the assessment, the attitude towards a computer assessment of posture, with the application of projection moire technique - Posturometr M, has been used. Results. The research results have been presented in diagram 1 - the course of changes in length average values of the5 foot arches of female population. To compare, diagram 2 presents the course of changes in length average values of the5 foot arches of both sexes. Conclusions • The first period is connected with intensive length development of I, II, III, IV and V longitudinal arches of the right and left foot and it takes place from the 5th to the 12th  year of life. The second period from the 12th  to the 16th year of life is the time of relative stabilization. The third one from the 16th  to the 18th year of life - the lengths decrease. • Longitudinal arches I, II and V of the right foot is longer than in the left foot from the 4th to the 6th year of life. In the period from the 6th to the 8th year of life the length of arches I, III and IV of the left foot is greater, in the period from the 8th  to the 17th year of life the length of arches I, II and V is greater in the right foot, the length of arch III up to the 16th year of life; next, all of them decrease in length. • Arches I, II, III, IV and V of both feet have a similar course of development. Arch I is the longest; next, respectively II and III, arches IV and V are definitely shorter.